Analisis Penerapan Green Accounting dan Kinerja Lingkungan Terhadap Harga Saham Melalui Profitabilitas Perusahaan - Evi Maria; Yosefine Elisabeth (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this research aims to see the effect of green accounting and environmental performance on stock prices through the mediation of profitability. The object of this research is mining companies listed on the Indonesian Stock Exchange and actively participating in the Program Penilaian Peringkat Kerja Perusahaan (PROPER) in the year 2015-2019 using the purposive sampling technique. This research uses secondary data, that is annual report and a financial report obtained from the website www.idx.co.id and environmental performance reports from the PROPER rating publication in the Keputusan Menteri Lingkungan Hidup dan Kehutanan. This research uses statistical analysis method Partial Least Square (PLS) with WarpPLS 6.0 software. The result of this research are: green accounting has negative but not significant effect on profitability, environmental performance has positive and significant effect on profitability, green accounting has positive and significant effect on stock price, environmental performance has negative and significant effect on stock price, profitability has positive and significant effect on stock price, green accounting has negative but not significant effect on stock price through profitability, environmental performance has positive and significant effect on stock price through profitability